PENGARUH STRES AKADEMIK DAN PENGGUNAAN GADGET DENGAN KEJADIAN NYERI KEPALA PRIMER PADA MAHASISWA KEDOKTERAN - Diana Khoirun Nida (2021)
During the pandemic, students were required to do ditance learning online. This indirectly requiredstudent to use gadget more often, and a lot of tasks could become academic stressor for students. That condition could disturb body's physiological balance which lead to primary headache. The study was conducted to see the effect of academic stress and gadget usage with the incidence of primary headache among students of the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta. This research was an analytical observational with cross sectional design. The research sample was 101 students of the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta in 2020 who met the research criteria. Consequtive sampling was used for this research. Academic stress variable were measured using academic questionnaires, gadget usage was measured by smartphone addicton questionanaire, and primary headache was measured by HO K-H and Ong BK-C questionnaire. Results showed that there was a significant relation between academic stress and primary headache with p value = 0.000 (p <0.05), and there was no significant relation between device use and primary headache with p value = 0.060 (p> 0.05). Multivariate test showed that the relation between academic stress has a stronger effect, with an OR value of 4.098.